2015
DOI: 10.3386/w21515
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Schools: Capital Spending, Facility Conditions, and Student Achievement

Abstract: Public investments in repairs, modernization, and construction of schools cost billions. However, little is known about the nature of school facility investments, whether it actually changes the physical condition of public schools, and the subsequent causal impacts on student achievement. We study the achievement effects of nearly 1,400 capital campaigns initiated and financed by local school districts, comparing districts where school capital bonds were either narrowly approved or defeated by district voters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…However, not all kinds of increases in school spending are related to improved educational outcomes. For example, studies using RD have found that increases in capital spending may not have such similar positive effects (Cellini et al, 2010; Martorell et al, 2016). Capital spending increases in schools and districts come from specific capital campaigns that are initiated by the local districts using referendums.…”
Section: Case Studies Of Quasi-experimental Research In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all kinds of increases in school spending are related to improved educational outcomes. For example, studies using RD have found that increases in capital spending may not have such similar positive effects (Cellini et al, 2010; Martorell et al, 2016). Capital spending increases in schools and districts come from specific capital campaigns that are initiated by the local districts using referendums.…”
Section: Case Studies Of Quasi-experimental Research In Educationmentioning
confidence: 99%
“…Capital spending increases in schools and districts come from specific capital campaigns that are initiated by the local districts using referendums. Martorell et al (2016) analyzed nearly 1,400 capital bond program referenda comparing districts where the referenda resulted in a narrow approval or failure. Because districts that barely passed or failed capital bonds passage are likely to be similar in most respects other than the “treatment,” selection bias into the treatment could be minimized.…”
Section: Case Studies Of Quasi-experimental Research In Educationmentioning
confidence: 99%
“…While CPTED offers promising results for improving school environments, the cost of renovating existing schools to meet ideal CPTED standards in a comprehensive manner would exceed most school districts' budget allowances (Schneider et al, 2000). Further, inequities in the funding of CPTED improvements might be disproportional, especially to students who come from families with limited political, social, or economic capital (Filardo, Bar, Cheng, Ulsoy, & Allen, 2010;Martorell, Stange, & McFarlin, 2016). Thus, there are significant systemic funding barriers to overcome in implementing CPTED in schools.…”
Section: Advantages Of Cpted Usementioning
confidence: 99%
“…For example, local school funding could be used primarily to support elective programs, such as extracurricular activities or music programs, which have important benefits outside the classroom but perhaps limited ability to increase student achievement (Costa-Giomi 2004; Kinney 2008; Rickard, Bambrick, and Gill 2012; Southgate and Roscigno 2009). Similarly, local school facilities funds—to maintain or improve school buildings, grounds, or equipment—could provide little benefit for daily school district operations or programs and hold little potential to increase average achievement (Martorell, Stange, and McFarlin 2016). However, if achievement among low-SES students is more dependent on school context (Sharkey 2010) or if facilities funding frees resources to spend on academic programs (i.e., money that would otherwise be used for temporary classrooms or maintenance of facilities in poor condition; Zimmer and Jones 2005), these local investments could improve achievement.…”
mentioning
confidence: 99%
“…Before 2013, school district election measures were “essentially the only source of local discretion” (Cellini, Ferreira, and Rothstein 2010:218). Given districts’ limited ability to increase their revenue in other ways, California school district election measures allow more precise estimates of local funding than in Texas, where Martorell and colleagues (2016) found null effects. The 1999-to-2013 period excludes years after the LCFF, a policy that may have changed the relationship between local funding elections and student achievement.…”
mentioning
confidence: 99%